(614) Perfect Dredging in Suez Canal: An Operations Research Study التكريك المثالي في قناة السويس: دراسة في بحوث العمليات - Ahmed H. El- Shatoury (معهد التخطيط القومى, 2026)
ملخص This study investigates the application of Operations Research techniques to dredging and maintenance activities in the Suez Canal with the objective of improving operational efficiency and maximizing productivity through the optimal utilization of available resources. Recognizing dredging as a critical activity for maintaining navigational depths and ensuring the safe and continuous movement of maritime traffic, the research focuses on analyzing dredge performance and developing both daily and annual maintenance schedules using the PERT (Program Evaluation and Review Technique) methodology. The study seeks to reduce unplanned downtime, improve equipment utilization, and enhance overall operational effectiveness. Quantitative models are employed to examine the relationships among the variables affecting dredging productivity, while statistical techniques such as correlation analysis, regression modeling, and analysis of variance are used to derive decision-support indicators. A trial model is also developed to maximize dredge output under conditions of perfect dredging by evaluating operational constraints and identifying optimal alternatives. Furthermore, the research addresses the selection of dredging plants and equipment according to technical, operational, and economic criteria. The analysis relies on actual operational data from the Suez Canal and utilizes computer-based calculations, including FORTRAN programs, to perform the required computations and simulations. The findings demonstrate that Operations Research methods provide an effective framework for planning dredging activities, increasing equipment productivity, reducing maintenance and operating costs, and supporting scientifically grounded decision-making. The study concludes that the integration of network planning techniques, statistical analysis, and mathematical modeling offers a comprehensive approach to managing dredging and maintenance projects in major waterways, leading to improved efficiency, productivity, and long-term operational sustainability. تتناول هذه الدراسة تطبيق أساليب بحوث العمليات في معالجة مشكلات التكريك والصيانة بقناة السويس بهدف رفع كفاءة التشغيل وتعظيم الإنتاجية مع الاستخدام الأمثل للموارد المتاحة. وتنطلق الدراسة من أهمية أعمال التكريك باعتبارها عنصرًا حيويًا للحفاظ على الأعماق الملاحية وضمان استمرار حركة السفن بكفاءة وأمان. وتركز على تحليل أداء كراكات التكريك وتحديد برامج الصيانة اليومية والسنوية باستخدام أسلوب PERT، بما يساهم في تقليل فترات التوقف غير المخطط لها وتحسين معدلات الإنجاز. كما تتناول الدراسة بناء نماذج كمية لتقدير العلاقات بين العوامل المؤثرة في الإنتاجية، واستخدام أساليب الارتباط والانحدار وتحليل التباين لاستخلاص المؤشرات الإحصائية اللازمة لاتخاذ القرارات التشغيلية. وتقدم نموذجًا تجريبيًا لتعظيم إنتاج الكراكة في حالة التكريك المثالي من خلال دراسة القيود الفنية والتشغيلية وتحديد أفضل بدائل العمل الممكنة. كذلك تبحث الدراسة معايير اختيار معدات ومنشآت التكريك الأكثر ملاءمة لطبيعة الأعمال المطلوبة، مع مراعاة الجوانب الاقتصادية والفنية والتشغيلية. واعتمد الباحث على البيانات الفعلية المتاحة بقناة السويس، إلى جانب تطبيقات الحاسب الآلي وبرامج FORTRAN لتنفيذ العمليات الحسابية والنماذج التحليلية. وتُظهر النتائج أن استخدام أساليب بحوث العمليات يسهم بصورة فعالة في تحسين تخطيط أعمال التكريك، ورفع كفاءة استغلال المعدات، وتقليل تكاليف التشغيل والصيانة، وتعزيز القدرة على اتخاذ قرارات مبنية على أسس علمية وكمية. وتخلص الدراسة إلى أن الدمج بين أساليب التخطيط الشبكي والتحليل الإحصائي والنمذجة الرياضية يوفر إطارًا متكاملًا لإدارة مشروعات التكريك والصيانة في الممرات الملاحية الكبرى، بما يدعم تحقيق مستويات أعلى من الكفاءة والإنتاجية والاستدامة التشغيلية.